PENERAPAN BANGUNAN HEMAT ENERGI PADA GEDUNG KESENIAN DI LUBUK PAKAM - Kasmiati; Moerni, Saufa Yardha (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
The design and construction fields are gradually conveying the green building discourse. The main cause is the use of buildings which use quite a lot of energy in their management. In 2019, the government began to launch a movement to apply green building concepts to government-owned buildings, one of which is to ensure that these buildings are classified as energy efficient. In its development, the concept of energy-efficient buildings is not only applied to government buildings but must also be applied to privately owned buildings. In this project, qualitative methods were used by carrying out a descriptive analysis of the art building objects linked to the application of energy-efficient building principles. Data collection using literature study methods in the form of energy-efficient building design theories and comparative studies related to buildings that apply energy-efficient building design principles. To achieve the goal of an energy-efficient building, the design of the Arts Building in Lubuk Pakam took a thin building design to allow as much use of natural lighting as possible. In rooms that require additional artificial lighting, the power requirements for each room are calculated and energy-saving lamps are used. In addition, using solar panels as an alternative source of electricity in buildings makes it possible to achieve energy savings used in the Arts Building in Lubuk Pakam.